Evolutionary selection processes : towards intra-organizational facets - Stańczyk-Hugiet, Ewa; Piórkowska, Katarzyna; Stańczyk, Sylwia; Strużyna, Janusz (Emerald points., 2019)
Natural evolution logic has been attracting the attention of researchers for years. More recently, it is being increasingly utilised in business and economics research where it provides the benefit of analysing a variety of organizational phenomena.This book provides new insights into the endogenous mechanism and the factors that influence it. It links the evolutionary approach, the process perspective, and the practice perspective in the area of strategy process, expanding the current research in multi-level logic within and beyond the organizations, and shows how the entire selection mechanisms behave at each level and how these mechanisms are connected across levels. This book: Takes an evolutionary perspective and focus on the selection suggesting that it can be explained not only by the interaction with the external environment, but also by internal - endogenous - factors. Proposes a multilevel selection mechanism that integrates the endogenous and exogenous pressures.Explains a managerial intervention and its effect on the adaptation mode concerning behavioral and cultural settings. Covers inter-organizational selection to build a complex picture of the selection.Evolutionary Selection Processes: Towards Intra-Organizational Facets will appeal to scholars and doctoral students in business and management, organization theory, organization behaviour, organizational change, and the strategic management field.